Дијагностичка вредност и корелација ризика серумског протеина за везивање масних киселина (Х-ФАБП) и остеопротерина (ОПГ) за хроничну срчану инсуфицијенцију - Zheng, Weifeng; Liu, Mingda; Xu, Sanduo; Xu, Wang (Journal of Medical Biochemistry, 2025)
Objective: To analyze the value of H-FABP and OPG in determining severity of heart function in those suffering from long-term heart failure. Method: 196 patients with persistent heart failure who were admitted to our hospital between June 2023 and October 2024 were chosen. A comparison was made between the three groups of chronic heart failure patients’ general clinical information, H-FABP, and OPG levels. The associations between OPG and H-FABP and various clinical forms of chronic heart failure, heart failure severity, and measurement markers related to echocardiography were examined. To assess NT-proBNP, H-FABP, and OPG detection alone and in combination for HFrEF and HFpEF in order to determine their diagnostic utility. Following their discharge, all patients were monitored for three to six months. Results: There was a positive correlation (r=0.61) between H-FABP and the NYHA classification, LA (r=0.46), LV (r=0.51), HS-TnT (r=0.31), NT-proBNP (r=0.58), SUA (r=0.38), etc., and negatively correlated with the LVEF (r=-0.76), NT-proBNP (r=0.49), etc., and negatively correlated with the LVEF (r=-0.60) (P<0.05). Binary logistic regression analysis of NT-proBNP, H-FABP, and OPG levels and endpoint events revealed that NT-proBNP had a high value in predicting endpoint events. The readmission rate and mortality rate of patients with chronic heart failure increased with increasing NT-proBNP concentration. Serum H-FABP and OPG all have high diagnostic value for HFrEF. Compared with the traditional biomarker NT-proBNP, H-FABP had a greater sensitivity (94.9%) and specificity (83.1%) in the diagnosis of HFrEF, whereas OPG had a greater sensitivity (92.3%) and a lower specificity (57.7%). H-FABP and OPG can significantly improve the sensitivity (86.44%) and specificity (89.74%) in the diagnosis of patients with HFrEF. Serum NT-proBNP, H-FABP and OPG all have high diagnostic value for HFpEF. Compared with the traditional biomarker NT-proBNP, H-FABP has greater sensitivity (91.7%) and specificity (82.0) in the diagnosis of HFpEF, whereas OPG has greater specificity (82.0%) and lower sensitivity (58.3%). Conclusion: The combined detection of H-FABP, OPG and NT-proBNP can be used as an important strategy for the early detection of heart failure patients’ declining cardiac function.